Design and FPGA-Based Implementation of A High Performance 64-Bit DSP Processor (International Journal of Engineering and Computer Science, 2018)
To meet the faster processing demand in consumer electronics, performance efficient DSP processor design is important. This paper presents a novel design and FPGA-based implementation of a 64 bit DSP processor to achieve high performance gain for reduced instruction set DSP processors. The proposed design includes a hazard-optimized pipelined architecture and a dedicated single cycle integer MAC to enhance the processing speed. Performance of the designed processor is evaluated against existing similar reduced instruction set DSP processor (MUN DSP-2000). Synthesis results and performance analysis of each system building component confirmed a significant performance improvement in the proposed DSP processor over the compared one.